Uma abordagem para otimização de estruturas tipo honeycomb para aplicação automotiva considerando simultaneamente impactos no plano e fora do plano - Frose, Luciano Rafael (2023)
Due to its mechanical characteristics, honeycomb-type structures are widely employed in absorbing impact energy. One application area is the automotive industry, where they can be utilized to enhance passenger vehicle safety in collision situations. These structures can have their shape optimized for a specific load and application. Most studies found in the literature currently optimize the structure when subjected to impact in one direction, neglecting loadings in other directions. The present work aims to propose a method for optimizing honeycomb-type structures considering two impact directions. This proposal seeks to ensure a structure capable of absorbing impact in any direction, given that in vehicular accidents, it is not possible to predict the direction of the collision. The proposed methodology aims to obtain an optimal geometry in a test situation separate from its final application. To avoid the high computational cost of direct optimization, the work employs metamodeling. The Abaqus software is used for simulation using the finite element method. This model is coupled with the optiSlang optimization software, which assists in creating the metamodel and subsequent optimization. An optimal geometry is considered one that has the highest specific energy absorbed from impact in both directions and with the lowest maximum impact force. After obtaining an optimal geometry, it is used as a basis for creating the final geometry added to the vehicular system. The evaluated application is a reinforcement for a vehicular bumper to reduce the peak deceleration at the moment of impact. It was possible to confirm that the auxetic honeycomb geometry performs better than regular honeycombs.